2020
DOI: 10.1038/s41598-020-64850-3
|View full text |Cite
|
Sign up to set email alerts
|

Implications of personality and parental education on healthy lifestyles among adolescents

Abstract: Several studies have shown an association between personality and health status. the aim of this study was to evaluate the association between personality traits, parental education and health-related lifestyles in a cohort of Spanish adolescents. this is a longitudinal study with a source population of 1,123 third-year students (aged 14-15) in secondary schools in Spain. At the baseline evaluation sociodemographic variables, parental education and personality (Big Five Questionnaire for Children) were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 55 publications
(69 reference statements)
3
13
0
1
Order By: Relevance
“…Outcomes that are consistent with ours in this respect have been observed in studies conducted in various countries [66][67][68][69]. Yañez et al have shown that low family educational level is associated with low adherence to the Mediterranean diet in adolescents [70]. It has been described that a low parent education level is associated with little knowledge of nutrition and a low level of awareness about aspects related to nutrition.…”
Section: Discussionsupporting
confidence: 88%
“…Outcomes that are consistent with ours in this respect have been observed in studies conducted in various countries [66][67][68][69]. Yañez et al have shown that low family educational level is associated with low adherence to the Mediterranean diet in adolescents [70]. It has been described that a low parent education level is associated with little knowledge of nutrition and a low level of awareness about aspects related to nutrition.…”
Section: Discussionsupporting
confidence: 88%
“…Notably, the present study also revealed conscientiousness to exhibit a significant negative association with alcohol intake for males, which is in line with previous literature [19,43,44].…”
Section: Discussionsupporting
confidence: 93%
“…The BFI-44 consists of 44 items and is the most commonly used. However, the shorter BFI-10 also achieved sufficient levels of validity and reliability: Discriminant and structural validity had been shown to be equivalent with those of the BFI- 44 and also reliability yielded satisfying results by capturing 70% of the variance and retaining 85% of the test-retest reliability of the BFI-44 [33].…”
Section: Assessmentsmentioning
confidence: 97%
“…This difference could be because mothers tend to have a more important physical and emotional presence at the home [30][31][32]. Other longitudinal studies, with older population also reported that parental socioeconomic status was consistently associated with healthy lifestyles (tobacco consumption, quality of diet) during adolescence in Spain [32,33].…”
Section: Discussionmentioning
confidence: 97%